Attributes of cancer patients admitted to the emergency department in one year - Sadik, Muallaoglu (Second Affiliated Hospital of Zhejiang University School of Medicine, 2014)
BACKGROUND: Cancer patients frequently visit the emergency department (ED) with various symptoms of cancer. The purpose of this study was to determine the clinical characteristics and 1-year survival rate of cancer patients in the ED of a university hospital. METHODS: We conducted a retrospective review of 408 cancer patients who visited the ED between January 2011 and December 2011. Patient information on demographics, chief complaints, findings, and survival was gathered from the hospital registry and corresponding health administration. RESULTS: The study included 240 (58.8%) males and 168 (41.2%) females with a median age of 57.9 years (range 19–87). Regarding cancer staging, 266 patients (65.3%) had metastatic disease and 142 (34.7%) had local and loco-regional disease. The hospitalization rate was 59.6%. The most common symptoms were shortness of breath (23.2%), pain (17.8%), fever (14.2%), and nausea/vomiting (14.4%). The most common cancer sites were the lung (32.5%), gastrointestinal system (25.4%), and breast (9.3%). The initial evaluation determined progressive disease (42.4%), chemotherapy effects (20.7%), infections (17.2%), radiotherapy effects (4.7%), extravasation (1.8%), anemia (1.4%), and unknown (11.3%). During follow up, 191 (46.8%) patients died after admission to the ED. The 1-year overall survival of all patients was 7.3 months. CONCLUSIONS: Symptom management in cancer patients is a complex multifaceted concern for the emergency physician. Because of the increasing prevalence of cancer patients, emergency physicians should develop consensus algorithms in collaboration with the relevant disciplines to manage the commonly encountered problems.